Approaches to personality types according to the Enneagram - Núñez Galvez, Cristian (2015)
This paper aims to show some of the theoretical review conducted as part of research for the degree of Master in Clinical Psychology and Health at San Marcos National University. This article takes as its axis the Enneagram as a typology of the personality, looking here a first approach to the arguments of who made such a statement, referencing the contributions of George Ivanovitch Gurdjieff, who introduced the Enneagram to the Western world, and Claudio Naranjo, a Chilean psychiatrist considered one of the pioneers of transpersonal psychology, who has provided support to the Enneagram as a tool of personality. Also, not to mention the Father Arnaldo Pangrazzi, religious Camilo, a member of the Associazione Italiana of Enneagramma.